The Influence of School Administrative Management on the Quality of the MTS (Putri) Ummul Quro Al-Islami School - Rahmawati Alwi; Syifa Fauziah (al-Afkar, Journal For Islamic Studies, 2024)
This research is based on the background of quality education, which is the demand and desire of all education stakeholders. Increasing the quality of education is very dependent on the processing of educational administration. With good administration, the school will have good quality in school progress. This research was conducted to determine school administration management and school quality at MTs (putri) Ummul Quro Al-Islami, as well as the influence of school administration management on school quality at MTs (putri) Ummul Quro Al-Islami. The study method used is a descriptive method, which uses a quantitative approach. The location of this study was MTs (putri) Ummul Quro Al-Islami Bogor with a sample size of 52 from a population of 52 people. The sampling technique is saturated sampling. The research results show that in general the percentage of school administration management is 81% in the very good category where the average value is 66.01, then the school quality is 75% in the very good category where the average value is 64.17. Based on the results of the analysis to prove the hypothesis, it is known that the T test shows that t-count is 9.476 > t-table 2.008 and sig. 0.000 < α 0.05. So it can be said that there is an influence between school administration management on school quality. With the level of influence of the independent variable and the dependent variable, it is 63.5%.